Cadmium (CD) in The Environment and Its Effect on The Animal Health and Productivity - ., Darmono (Indonesian Animal Sciences Society, 1999)
Cadmium (Cd) is a nonesential element which often cause of environmental pollution and toxic effect to the animal and man. Cadmium also has an acummulative effect in the tissue of biological life, as a consequence it cause contamination in feed and food such as grass, grain and animal tissue. Because ofthat Cd enter into food chain which consumed by animal or human. In the animal Cd can cause of tissue damage and produced acute or chronic toxicity, as consequence cause of disease and decrease of animal production. Key words : Cadmium, environment, animals